Pelatihan Membaca sebagai Upaya Meningkatkan Literasi Anak Nelayan: Reading Training as an Effort to Literacy of Fisherman’s Children - Riyanti, Asih; Fauziyyah, Nurul Hanna (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Early childhood and elementary school reading training is essential in forming a literacy foundation for children. This training activity aims to improve children's reading literacy in Tanjung Pasir Tarakan Village, North Kalimantan. The training methods used are demonstration and training. The training activities are designed through creative and interactive activities to stimulate children in reading activities and help them understand their meaning. The stages of this training activity consist of the initial stage, the implementation stage, and the final stage. The initial stage is a form of planning before the reading training is carried out; the implementation stage is the process of reading training activities. Activities include demonstrations and direct practice of reading with media through picture stories, letter recognition, and short stories. The final stage is to monitor and evaluate the implementation of the activities that have been carried out. The results of the implementation of this activity show that the fishermen's children are very enthusiastic about participating in the reading training. Children show a significant increase in interest in reading activities; children can already recognize letters, their vocabulary increases, they can read simple words, and they can already read short stories (for lower-grade children). This training shows the good impact of this reading training program on children's reading abilities. This training is an early milestone for the development of children's literacy.